Burns in pandemic times – The Graz way towards COVID-19 and back. Issue 1 (February 2021) - Nischwitz, Sebastian P.; Popp, Daniel; Sawetz, Isabelle; Smolle, Christian; Tuca, Alexandru-Cristian; Luze, Hanna; Kamolz, Lars-Peter
Highlights: Large hospitals with burn units face particular challenges during the COVID-19 pandemic. The strategy of the University Hospital Graz, including the way back to normality are presented. Re-booting measures need to be elaborated as carefully as lock-down measures. Measures include infrastructure, patients and staff and need to be coordinated with local authorities. Abstract: The first half of the year 2020 has been shaped by quarantines and lock-downs all over the world. The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic, that slowed down not only social interactions and economy, but also medical and health care. Governments and hospitals were forced to create ad hoc emergency plans maintaining the balance between an adequate participation in collective response of shutting-down to avoid a further spreading of the virus, while preserving the ongoing acute care and simultaneously being able to react to an imminent overextension with a collapse of capacities. The University Hospital Graz is one of the largest hospitals in Austria. As transregional trauma and burn centre it provides care for people from all over Austria and faced special challenges. We present the strategy of the University Hospital Graz in dealing with the COVID-19 pandemic and the way back to (new) normality. The strategy includes infrastructural, patient-centred and staff-centred measures. The continuously low numbers of new infections in Austria allowed a loosening of the lock-down measures already. Particular attention has to be paid to attentive screening of patients and triaging of surgeries during the re-boot. The re-boot needs to be slow and steady to reduce the risk of an infectiological relapse. Once this pandemic is defeated, a careful re-evaluation of the different internationally applied strategies should be performed to be prepared for the future.